Mobile Optical Device For Quantitative Analysis of Photosynthetic Microbes - Anthanyomthu, Neesha Sabrina (2017)
Photosynthesis microbes are widely used in many applications thus quantification of photosynthesis microbes is required to determine the density of the microbes in particular condition or environment. The conventional methods that are available for quantification are not rapid and portable. Hence, the focus of this project is to use a smart device with red green blue (RGB) light ambient sensor to quantify four distinct species of photosynthesis microbes (H. pluvialis and C. vulgaris, A. platensis and A. cylindrica) as smart device are highly portable. Correlation studies was done between cell density obtained from direct cell count and OD measurement by conventional spectrophotometer at λ = 700 nm, 625 nm and 470 nm. The results were later correlated to the lux and RGB reading obtained red green blue (RGB) light ambient sensor by correlating lux with cell density and OD measurement and RGB reading correlating with cell density. Based on the correlation equation and graphs, there was correlation between the cell density and OD measurement at λ = 700 nm, 625 nm and 470 nm with spectrophotometer. The lux was correlated with both reading from the cell density and OD measurement. However, there was no correlation between RGB reading and cell density. Thus, the photosynthetic organisms cannot be quantified by the RGB readings produced by the sensor on the smart device. However, the quantification can be accurately done by taking lux reading produced by the sensor.